Paleoenvironments of the Valentín Formation (Late Quaternary) in the Ullum-Zonda Valley, Precordillera of San Juan, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2020)
The Valentín Formation (late Pleistocene-middle Holocene) outcrops in the Ullum-Zonda valley located in the south-central region of the Province of San Juan, in the Argentine Republic, about 20 km west of the capital city of San Juan. It is a tectonic depression in which two fold and thrust belts with different levels of detachment and opposite vergence converge and collide: to the west, the east verging thin-skinned Central Precordillera, and to the east, the west verging thick-skinned Eastern Precordillera (Rolleri, 1969; Baldis et al., 1979; Ortiz and Zambrano, 1981; Ramos, 1988, Allmendinger et al., 1990; Jordan et al., 1993; among others). The outcrops of the Valentín Formation have a surface area of 3.6 km2 and are scattered in an area of ~110 km2 (Fig. 4) to the north, east, south, and southwest of the Ullum-Zonda valley. The paleoenvironmental evolution of these sequences is not yet clearly understood. Consequently, it has been almost impossible to determine the paleogeography and paleoclimatic conditions in this valley during the late Pleistocene-Holocene climatic transition. This study constitutes the first attempt to address this issue.Traditionally, the Valentín Formation has been interpreted as a lacustrine-palustrine environment associated with the San Juan River (e.g., Groeber and Tapia, 1926; Pandolfo, 1975; Salinas, 1979; García, 1996; Colombo et al., 2000; Suvires and Gamboa, 2011; Blanc, 2014; Blanc and Perucca, 2017; among others), an antecedent stream that descends from the Andes Cordillera. Following the three-component scheme to represent sediment movement along mountain valleys in Precordillera from Suriano et al. (2014) (Fig. 3), the San Juan River behaves as a sedimentary transference system for the intermountain basins developed along the narrow axial valleys between the numerous ranges of the Precordillera. This river has a glacial-nival regime with the peak of maximum runoff between December and January. It has an average annual flow of 60 m3/sec (Subsecretaría de Recursos Hídricos, 2004), registering millenary floods that can exceed 1,000 m3/sec (Perucca and Esper, 2009).In this study, we introduce a lithofacial, stratigraphic and paleoenvironmental analysis of the Valentín Formation together with a paleogeographic and paleoclimatic characterization of the Late Pleistocene and Early to Mid-Holocene in the Ullum-Zonda tectonic depression, based on sedimentological, geomorphological, and geochronological data (conventional radiocarbon, AMS, and OSL). Following the scheme proposed by Blanc and Perucca (2017; Fig. 4), the study area was divided into six sectors based on the spatial distribution of the Valentín Formation outcrops to facilitate a neat description and analysis. We carried out a detailed lithofacies analysis (Tables 2, 3, and 4) in five stratigraphic logs in sectors 1 (logs PB-VI and PB-COU), 2 (PB-FVZ log), and 5 (logs PB-DS1 and PB-DS2) (Fig. 5), and control observations in sectors 3, 4, and 6. Log description and analysis were made using the methodology proposed by Miall (1977), Allen (1983), Miall (1985; 1996; 2006) with modifications. The data obtained for the characterization of facies included: the thickness of horizons or layers, limiting surfaces, texture, structure, and carbonates. The texture was determined using classical soil manipulation methods to analyze its plasticity (Thien, 1979). The relative content of CaCO3 was determined from the sediment reaction (weak, moderate, or strong) in HCl diluted to 10%. Genetically related facies were grouped into facies associations (Table 3) considering as such a body of rock larger than a facies, characterized by its geometry (internal and external), the arrangement of its limiting surfaces (in the case of architectural elements), and the facies that compose it (Miall, 1977; Allen and Allen, 2005; Bridge and Demicco, 2008). Sixteen facies associations were defined and grouped into eight subenvironments representative of five sedimentary environments (Table 4). The geomorphological analysis consisted of the study of the landforms using satellite images, aerial photos, and digital elevation models (DEM of the Argentinian National Geographic Institute of 5 and 30 m resolution) together with field surveys where we observed the contact relationships between the different landforms and their morphogenetic processes. For the geochronological analysis, we used available numerical ages (Blanc and Perucca, 2017) (Table 1) from 14C dating of organic sediments by conventional and AMS techniques. Based on the obtained data, we constructed an artistic “paleo-satellite image” of the Ullum-Zonda valley using photographic montage techniques to approximately represent the paleogeography of this valley for the early Holocene (Greenlandian, ~ 9,300 years BP) (Fig. 10).Blanc and Perucca (2017) divided the Valentín Formation into two chronostratigraphic units: a late Pleistocene age (16,700–15,200 years BP) unit and an early to middle Holocene (9,475–7,685 years BP) unit. The stratigraphic relationship between these units has not been established. Results revealed that the Valentín Formation deposits show numerous flow sedimentary structures associated with rapidly aggrading anastomosed and ephemeral meandering river systems with thick unconfined mud-clay-sandy floodplains, vertical accretion, aeolian deposition, and a low gradient (Order C, Nanson and Croke, 1992). A subordinate share of these deposits indicated the existence of a small (
Keywords: facies; arid climates; tectonic depression; Pleistocene-Holocene; fluvial systems; Central Andes